1981
DOI: 10.1111/j.1471-0528.1981.tb01226.x
|View full text |Cite
|
Sign up to set email alerts
|

The Titanium/Silicone Rubber Clip for Female Sterilization

Abstract: A composite titanium/silicone rubber clip has been developed for female sterilization. The 12.7 mm long metal clip is lined with silicone rubber and is bent round the Fallopian tube by means of an applicator that can be used laparoscopically. As tubal necrosis occurs, the rubber expands to keep the lumen blocked. The tube eventually divides and the stumps heal, closed. Since the Mark 3 version of the clip was introduced, over 5700 women in several countries have been sterilized. The first 540 British women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…Although the titanium clip was not available at the time of the study, the efficacy of the titanium clip has been well established. 5,6 However, with regard to postpartum use, data to support routine use of the clip are less clear. 3 Only eight postpartum women were included in the original efficacy trial, and their outcomes were not reported separately.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the titanium clip was not available at the time of the study, the efficacy of the titanium clip has been well established. 5,6 However, with regard to postpartum use, data to support routine use of the clip are less clear. 3 Only eight postpartum women were included in the original efficacy trial, and their outcomes were not reported separately.…”
Section: Introductionmentioning
confidence: 99%
“…4 The use of occlusive devices, such as a ring or clip placed via laparoscopy, are commonly used methods for interval sterilisation (defined as tubal sterilisation at least 6 weeks following a birth), but have also been used in the postpartum period. 5 The use of an occlusive device, rather than transecting and ligating with suture, has the advantages of speed and ease of procedure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations